The Relation of Formal and Semantic Aspects of Lexical Borrowings in the Process of Adaptation - Svobodová, Diana; Bańko, Mirosław (Bohemica Olomucensia, 2016)
The paper deals with formal and functional aspects of loanwords, which either still have their native synonyms in Polish and Czech as recipient languages, or which are used in these languages in variant forms on different levels of adaptation. We assume the structure and form of a word is not irrelevant: the form can bear on at least a connotative meaning, it can direct the word's development and, in cases of lexical borrowings, it can influence the way these words become adapted in the recipient languages. In case of the synonyms, we focus on divergence of their functional potential and on their etymological, expressive and associative features, the last one also with the help of psycholinguistic methods.
Keywords: synonym; lexical borrowing; word form; formal adaptation; semantic meaning; language function; psycholinguistics